A lithium ion battery containing a solid electrolyte and a method for preparing the same

By adopting new solid-state electrolytes and in-situ polymerization technology in lithium-ion batteries, the problems of poor battery rate performance and poor charging and discharging performance in room temperature are solved, and high-performance lithium-ion batteries at room temperature are achieved.

CN115763964BActive Publication Date: 2025-04-15四川启睿克科技有限公司 +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211618591.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-15
Publication Date
2025-04-15
Estimated Expiration
2042-12-15

AI Technical Summary

Technical Problem

The existing solid electrolytes have problems in lithium-ion batteries with poor contact with the electrode interface and low ion conductivity, resulting in poor battery rate performance and poor charging and discharging performance at room temperature.

Method used

A lithium-ion battery preparation method containing a new solid electrolyte is adopted. By mixing N,N-dimethylformamide and acetone, polyvinylidene fluoride-hexafluoropropylene copolymer, Al2O3, lithium bistrifluoromethanesulfonylimide and lithium difluoroxalate borate, the film is poured into a film by mixing N,N-dimethylformamide and acetone, the interface stability between the electrolyte membrane and the electrode sheet is improved.

Benefits of technology

The rate performance of lithium-ion batteries has been significantly improved and successful application at room temperature has been achieved. The cycling performance of the battery has been significantly improved at both high temperature and room temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115763964B_ABST
    Figure CN115763964B_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery including a solid electrolyte and a preparation method thereof, comprising the following steps: N, N-dimethylformamide and acetone solvent are mixed evenly, then polyvinylidene fluoride-hexafluoropropylene copolymer, Al2O3, bistrifluoromethanesulfonyl imide lithium and difluoro oxalate lithium borate are added, the mixed slurry is poured on a glass plate after stirring evenly, and then dried to form a film to obtain an electrolyte membrane for standby use; halogenated cyclic lactone monomer, amide monomer, polyvinyl alcohol, polyethylene oxide are dissolved in a liquid lithium ion electrolyte, and then an initiator is added, and after mixing evenly, a mixed solution is obtained; the mixed solution is matched with positive and negative electrodes and an electrolyte membrane for battery assembly; after the battery assembly is completed, in-situ polymerization is performed. This method can significantly improve the rate performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of lithium battery electrolytes, and in particular to a lithium ion battery containing a solid electrolyte and a preparation method thereof. Background Art

[0002] Solid electrolytes have received widespread attention for their efforts to solve the safety issues of lithium-ion batteries. However, due to the poor contact between solid electrolytes and the electrode interface and the low ionic conductivity of the solid electrolytes themselves, this technology is still in the research and development stage. Generally, solid electrolytes are mainly divided into two categories: polymers and inorganic substances. Polymer electrolytes are relatively soft and have good contact with the pole pieces, but their ionic conductivity is low, resulting in almost no normal charging and discharging of the battery at room temperature and poor rate performance. Inorganic electrolytes have high conductivity, but poor contact with the pole pieces, which places more stringent requirements on the battery assembly process.

[0003] Inorganic substances mainly include sulfides and oxides, and polymers are mainly polyethers, polycarbonates, etc., represented by PEO. Polycarboxylates are rarely reported. Since polycarboxylates have advantages such as excellent lithium ion transport capacity and a wide electrochemical stability window, they can be used as a favorable alternative to polyether electrolytes. Patent CN 111342123 A describes the preparation and application of a selectively wettable polymer electrolyte. The main core point of this patent is a polymer electrolyte containing polyvinylidene fluoride materials and polycarboxylates that selectively absorb sulfone small molecule additives, and its preparation method and application in quasi-solid-state lithium batteries. Among them, the polycarboxylates described in this patent mainly refer to carboxylate monomers containing unsaturated bonds, and the polymerization site is the unsaturated bond for addition polymerization. Patent CN 113461924 A proposes a one-pot method for synthesizing polyester block copolymer-based polymer electrolytes. Through styrene monomers, cyclic lactone monomers, poly(ethylene glycol) methacrylate, and the use of suitable difunctionalized chain transfer agents and free radical initiators, reversible addition-fragmentation transfer polymerization and cyclic lactone ring-opening polymerization reactions can be combined in one pot. A solid polymer electrolyte with excellent mechanical strength and electrochemical properties is synthesized. Patent CN 114920918 A proposes an in-situ method to synthesize a copolymer electrolyte in one step, which can improve the interface stability between the electrolyte and the lithium negative electrode, but the electrolyte can only be used normally at high temperature (60°C), and the room temperature performance is not mentioned. Patent 202110786577.X proposes a polyester brush-shaped polymer electrolyte that can improve the cycle performance of the battery and has good compatibility with metallic lithium. However, the synthesis method is complicated, has high experimental requirements, is easy to introduce impurities, and cannot be supplied in large quantities. In addition, the obtained film is relatively thick (80 microns), while the commonly used commercial diaphragm is about 20 microns. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a lithium ion battery containing a solid electrolyte and a preparation method thereof, and prepares a series of lithium ion batteries containing a novel solid electrolyte, which can significantly improve the rate performance of the battery and achieve successful application.

[0005] The present invention provides the following technical solutions:

[0006] A method for preparing a lithium-ion battery containing a solid electrolyte comprises the following steps: (1) N,N-dimethylformamide and acetone are mixed evenly to obtain a mixed solvent, and then polyvinylidene fluoride-hexafluoropropylene copolymer, Al2O3, lithium bis(trifluoromethanesulfonyl imide) and lithium difluorooxalate borate are added, and the mixed slurry is cast on a glass plate after stirring evenly, and then dried to form a film to obtain an electrolyte membrane for standby use; (2) halogenated cyclic lactone monomer, amide monomer, polyvinyl alcohol, and polyethylene oxide are dissolved in a liquid lithium-ion electrolyte, and then an initiator is added and mixed evenly to obtain a mixed solution; the mixed solution is matched with a positive and negative electrode and an electrolyte membrane to assemble a battery; (3) after the battery is assembled, in-situ polymerization is performed to obtain a lithium-ion battery containing a solid electrolyte. The main principle of in-situ polymerization is:

[0007]

[0008] A further technical solution is that in step (1), the mass ratio of N,N-dimethylformamide to acetone is 5:2, the amount of polyvinylidene fluoride-hexafluoropropylene copolymer added accounts for 10wt% of the mass of the mixed solvent, the amount of Al2O3 added accounts for 1wt% of the mass of the mixed solvent, the amount of lithium bistrifluoromethanesulfonyl imide added accounts for 1-3wt% of the mass of the mixed solvent, and the amount of lithium difluorooxalatoborate added accounts for 0.1-1wt% of the mass of the mixed solvent.

[0009] A further technical solution is that in step (1), the stirring temperature is 40 to 50° C. and the stirring time is 1 to 3 hours.

[0010] A further technical solution is that the drying temperature in step (1) is 70-80°C.

[0011] A further technical solution is that in the mixed solution in step (2), the mass fraction of the halogenated cyclic lactone monomer is 20wt% to 70wt%, the mass fraction of the amide monomer is 1wt% to 10wt%, the mass fraction of the polyvinyl alcohol is 1 to 5wt%, the mass fraction of the polyethylene oxide is 1 to 5wt%, and the mass fraction of the initiator is 0.1wt%.

[0012] A further technical solution is that the halogenated cyclic lactone monomer in step (2) is one or more of the following structures:

[0013]

[0014] Wherein, X is F, Cl, Br or I.

[0015] A further technical solution is that the amide monomer in step (2) is one or more of N,N-methylenebisacrylamide or hexamethylenebisacrylamide.

[0016] A further technical solution is that the temperature of the in-situ polymerization in step (3) is 50-60° C. and the time is 5-6 hours.

[0017] A further technical solution is that the positive electrode material in step (2) is

[0018] In step (2), the positive electrode material is selected from LiNi 0.8 Co 0.1 Mn 0.1 02. LiNi 0.5 Co 0.2 Mn 0.3 Any one of O2 and LiFePO4, the negative electrode material is a silicon-based negative electrode material, and the silicon-based negative electrode material can also be matched with metallic lithium

[0019] The present invention also provides a lithium ion battery comprising a solid electrolyte, which is prepared by the above preparation method.

[0020] Compared with the prior art, the present invention has the following beneficial effects: the strong interaction between the -CF2 group and the -COC- group in the electrolyte-based membrane PVDF-HFP of the present invention can improve the adhesion between solid electrolytes and reduce contact impedance; the quasi-solid electrolyte membrane contains PVA, and the silicon-based negative electrode material contains PAA binder, and the two can be in-situ grafted during the heating process to reduce the contact resistance between the electrolyte membrane and the pole piece. In addition, the silicon-based negative electrode itself has a large volume change during the charging and discharging process. The grafting of PVA and PAA can form a buffer layer, which can resist the volume change of the material during the charging and discharging process and ensure the material performance; the in-situ polymerized gel electrolyte can construct a better positive and negative electrode ion path, improve the interface stability between the electrolyte and the pole piece, and improve the compatibility of the electrolyte membrane with the positive and negative electrodes. Due to the salt hydrolysis and cationic coordination synergistic effect of the acylamino group (O=C-NH) and the ester group (-COOR), the transmission of alkali metal ions can be effectively improved, the transfer number of alkali metal ions can be increased, and the rate performance of the battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is the high temperature cycle diagram of the full battery of Example 1-6;

[0022] Figure 2 The normal temperature cycle diagram of the full battery of Example 1-6;

[0023] Figure 3 This is the morphology of the electrolyte base membrane. DETAILED DESCRIPTION

[0024] The present invention is further described below by way of examples, which are for illustrative purposes only and do not limit the scope of the present invention. The test methods in the following examples without specifying specific conditions are usually carried out under conventional conditions.

[0025] Example 1

[0026] Preparation of base film: 10wt% PVDF-HFP was dissolved in 5:2 (mass ratio) DMF and acetone, 1wt% LiTFSI and 1wt% LiDFOB were added, and stirred at 50℃ for 2h. The slurry was poured onto a glass plate, dried at 60℃, cut into 19mm small discs, and assembled with snap-on circuits and tested for performance.

[0027] Example 2

[0028] Dissolve 1:1 (mass ratio) of PVA and PEO and 10wt% PVDF-HFP in 5:2 (mass ratio) of DMF and acetone, add 1wt% LiTFSI and 1wt% LiDFOB, stir at 50℃ for 2h, pour the slurry onto a glass plate, dry at 60℃, cut into 19mm small discs, match the positive and negative electrodes, and assemble a button cell.

[0029] Example 3

[0030] 2g 0.2 g of N,N'-methylenebisacrylamide, 0.05 g of PVA, and 0.1 g of PEO were dissolved in 5 mL of liquid electrolyte, 0.005 g of AIBN was added, and after mixing evenly, 40 μl was taken out to assemble the battery with the base film of Comparative Example 1, silicon-based negative electrode, and 811 positive electrode.

[0031] Example 4

[0032] 3g 0.5 g of N,N'-methylenebisacrylamide, 0.1 g of PVA, and 0.1 g of PEO were dissolved in 5 mL of liquid electrolyte, 0.005 g of AIBN was added, and after mixing evenly, 40 μl was taken out and matched with the base film of comparative example 1, silicon-based negative electrode, and 811 for battery assembly.

[0033] Example 5

[0034] 3.5g 0.2 g of hexamethylenebisacrylamide, 0.05 g of PVA, and 0.2 g of PEO were dissolved in 5 mL of liquid electrolyte, 0.005 g of AIBN was added, and after mixing evenly, 40 μL was taken out to assemble the battery with the base film of Comparative Example 1, silicon-based negative electrode, and metallic lithium.

[0035] Example 6

[0036] 3g 0.2 g of N,N'-methylenebisacrylamide, 0.05 g of PVA, 0.1 g of PEO, and 0.1 g of LLZTO were dissolved in 5 mL of liquid electrolyte, 0.005 g of AIBN was added, and after mixing evenly, 40 μL was taken out to assemble the battery with the base film of Comparative Example 1, silicon-based negative electrode, and metallic lithium.

[0037] Example 7

[0038] 3g 0.2 g of N,N'-methylenebisacrylamide, 0.1 g of PVA, and 0.1 g of PEO were dissolved in 5 mL of liquid electrolyte, 0.005 g of AIBN was added, and after mixing evenly, 40 μL was taken out to assemble the battery with the base film of comparative example 1, silicon-based negative electrode, and metallic lithium as the counter electrode.

[0039] After the batteries in the above examples were assembled, they were stored at 50°C for 5 hours before testing. The batteries in Examples 1-6 were activated by cycling at 0.1C for 4 cycles, and then cycled at 1C. The battery charge and discharge cut-off voltage was 3-4.2V. The cycling results at high temperature are shown in Figure 1. Figure 1 As shown, the cycle results at room temperature are as follows Figure 2 The charge and discharge cut-off voltage of Example 7 is 3-0.005V. The battery is activated at 0.1C for 4 cycles and then cycled at 0.3C. The capacity retention rate after 200 cycles reaches more than 90%.

[0040] The electrochemical performance statistics of Examples 1-6 are shown in Table 1.

[0041] Table 1 Electrochemical performance data of Examples 1-6

[0042]

[0043] Although the present invention is described herein with reference to the illustrative embodiments of the present invention, the above embodiments are only preferred embodiments of the present invention, and the embodiments of the present invention are not limited to the above embodiments. It should be understood that those skilled in the art can design many other modifications and embodiments, which will fall within the scope and spirit of the principles disclosed in this application.

Claims

1. A method for preparing a lithium ion battery containing a solid electrolyte, characterized in that: The method comprises the following steps: (1) mixing N,N-dimethylformamide and acetone uniformly to obtain a mixed solvent, then adding polyvinylidene fluoride-hexafluoropropylene copolymer, Al2O3, lithium bis(trifluoromethanesulfonyl imide) and lithium difluorooxalate borate, stirring uniformly, casting the mixed slurry on a glass plate, and then drying to form a film to obtain an electrolyte membrane for standby use; (2) dissolving a halogenated cyclic lactone monomer, an amide monomer, polyvinyl alcohol and polyethylene oxide in a liquid lithium ion electrolyte, then adding an initiator and mixing uniformly to obtain a mixed solution; assembling a battery by combining the mixed solution with a positive and negative electrode and an electrolyte membrane; and (3) after the battery assembly is completed, performing in-situ polymerization to obtain a lithium ion battery containing a solid electrolyte.

2. The method for preparing a lithium-ion battery containing a solid electrolyte according to claim 1, characterized in that: In step (1), the mass ratio of N,N-dimethylformamide to acetone is 5:2, the amount of polyvinylidene fluoride-hexafluoropropylene copolymer added accounts for 10wt% of the mass of the mixed solvent, the amount of Al2O3 added accounts for 1wt% of the mass of the mixed solvent, the amount of lithium bistrifluoromethanesulfonyl imide added accounts for 1-3wt% of the mass of the mixed solvent, and the amount of lithium difluorooxalatoborate added accounts for 0.1-1wt% of the mass of the mixed solvent.

3. The method for preparing a lithium-ion battery containing a solid electrolyte according to claim 1, characterized in that: In step (1), the stirring temperature is 40 to 50° C. and the stirring time is 1 to 3 hours.

4. The method for preparing a lithium-ion battery containing a solid electrolyte according to claim 1, characterized in that: The drying temperature in step (1) is 70-80°C.

5. The method for preparing a lithium-ion battery containing a solid electrolyte according to claim 1, characterized in that: The mass fraction of the halogenated cyclic lactone monomer in the mixed solution in step (2) is 20wt% to 70wt%, the mass fraction of the amide monomer is 1wt% to 10wt%, the mass fraction of polyvinyl alcohol is 1 to 5wt%, the mass fraction of polyethylene oxide is 1 to 5wt%, and the mass fraction of the initiator is 0.1wt%.

6. The method for preparing a lithium-ion battery containing a solid electrolyte according to claim 1, characterized in that: The halogenated cyclic lactone monomer in step (2) is one or more of the following structures: Wherein, X is F, Cl, Br or I.

7. The method for preparing a lithium-ion battery containing a solid electrolyte according to claim 1, characterized in that: The amide monomer in step (2) is one or more of N,N-methylenebisacrylamide or hexamethylenebisacrylamide.

8. The method for preparing a lithium-ion battery containing a solid electrolyte according to claim 1, characterized in that: The temperature of the in-situ polymerization in step (3) is 50-60° C. and the time is 5-6 hours.

9. The method for preparing a lithium-ion battery containing a solid electrolyte according to claim 1, characterized in that: In step (2), the positive electrode material is selected from LiNi 0.8 Co 0.1 Mn 0.1 02. LiNi 0.5 Co 0.2 Mn 0.3 Any one of O2, LiFePO4, the negative electrode material is a silicon-based negative electrode material; or the negative electrode material is a combination of silicon-based negative electrode material and metallic lithium.

10. A lithium ion battery comprising a solid electrolyte, characterized in that: The compound is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Selective infiltration polymer electrolyte as well as preparation and application thereof

    CN111342123A

  • Polyester block copolymer, one-pot synthesis method and application

    CN113461924A

  • Polyester-based brush-shaped polymer electrolyte and preparation and application thereof

    CN113527642A

  • Block copolymer electrolyte as well as in-situ preparation method and application thereof

    CN114920918A

  • Polyolefin composite membrane and preparation method thereof as well as lithium ion battery

    CN104124416A